Field experimental and numerical study on the formation and frost heave development of frozen soil under rapid freezing - Fuchen Teng; Yong Cheng Sie; Chihping Kuo (Case Studies in Construction Materials)
Compared with natural soils, frozen soil, which is the primary product of artificial ground freezing (AGF) engineering, is typically impermeable and exhibits superior shear strength. This study investigated the formation and frost heave behavior of frozen soil material under rapid freezing conditions using liquid nitrogen (LN2). Unlike most studies, which have focused on the slower brine freezing method, this research highlights the unique effects of the faster LN2 freezing method. A six-day field experiment was conducted, which integrated nondestructive monitoring techniques such as electrical resistivity tomography (ERT). This method enables detailed spatial and temporal visualization of subsurface resistivity changes. Numerical simulations were performed using the frozen and unfrozen soil model (FUS) to analyze the thermalhydraulicmechanical interactions within the soil during freezing. The results revealed that the temperature of the soil within a distance of 0.5 m from the freezing pipes fell below zero in only six days, resulting in a maximum displacement of 60 mm in the ground. Discontinuous frost heave displacements also occurred. Numerical simulations revealed discrepancies between the simulated and measured data because the soil at depths of 4–7 m was not completely frozen due to the presence of soil and groundwater conditions that were resistant to freezing. This study bridges the knowledge gap in LN2 artificial ground freezing and provides practical guidance for its application under challenging geotechnical conditions.